Electrolyte solution, secondary battery, and electric device
Patent Information
- Application Number
- CN202380066605.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-18
- Publication Date
- 2025-04-25
AI Technical Summary
The existing electrolyte has high impedance in lithium batteries and cannot meet the demand for improving battery performance. In particular, it causes lithium deposition in the negative electrode during the charging process and affects the life of the battery cell.
An electrolyte solution including a cyclic sulfate ester compound and a metal ion additive is used to reduce the interface resistance and improve the rate performance of the battery by forming a stable solid electrolyte phase interface film (SEI).
By forming a stable SEI film, the interface resistance is significantly reduced, the rate performance and electrochemical performance of the battery are improved, and the service life of the battery is extended.
Smart Images

Figure CN119895617A_ABST
Abstract
Description
Electrolyte, secondary battery and electrical device Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to an electrolyte, a secondary battery, and an electrical device. Background Art
[0002] In recent years, with the development of secondary battery technology, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power, and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, and other fields. As the application fields of secondary batteries have achieved great development, the requirements for their battery performance have also been put forward.
[0003] During battery charging, the electrolyte continuously reduces at the negative electrode. To reduce side reactions at the negative electrode, attempts have been made to add various compounds to the electrolyte to form a passivation layer on the negative electrode surface, also known as the solid electrolyte interphase (SEI). Research has shown that forming a uniform, dense, stable, low-impedance, and well-adhesive solid electrolyte interphase (SEI) improves the electrochemical properties of the battery and enhances its performance. However, existing electrolyte systems have high impedance and cannot meet the requirements for improving battery performance.
[0004] Summary of the Invention
[0005] The present application is made in view of the above-mentioned problems, and its purpose is to provide an electrolyte, which includes a cyclic sulfate compound represented by Formula I and a metal ion additive. The cyclic sulfate compound and the metal ion additive contribute to the formation of a stable SEI film, thereby contributing to improving the rate performance of the battery.
[0006] In a first aspect of the present application, an electrolyte is provided, comprising a cyclic sulfate compound represented by Formula I and a metal ion additive.
[0007] In formula I, R1, R2, R3, and R4 are each independently selected from the structure shown in formula II, a hydrogen atom, a C 1- One of a C6 alkyl group, a halogen atom, a C1-C3 haloalkyl group, a C1-C3 alkoxy group, a C1-C3 haloalkoxy group, a double bond, an ester group, a cyano group, and a sulfonic acid group, and R1, R2, R3, and R4 are not simultaneously selected from a hydrogen atom;
[0008] In formula II, R5 and R6 are each independently selected from hydrogen atom, C 1- One of a C6 alkyl group, a halogen atom, a C1-C3 haloalkyl group, a C1-C3 alkoxy group, a C1-C3 haloalkoxy group, a double bond, an ester group, a cyano group and a sulfonic acid group, and a wavy line indicates a bonding position.
[0009] On the one hand, the introduction of cyclic sulfate compounds into the electrolyte facilitates the formation of a stable SEI film. During battery charging, the cyclic sulfate groups help form a sulfite-based inorganic film between the electrolyte and the negative electrode, while the R1, R2, R3, or R4 groups help form a resilient organic film between the electrolyte and the negative electrode. For example, by introducing alkyl / alkoxy groups into the R1, R2, R3, or R4 groups, a resilient SEI film with longer organic chains can be generated on the negative electrode side to cope with the volume changes on the negative electrode side during cycling, thereby avoiding or reducing SEI film damage and improving SEI film stability. Furthermore, the introduction of F- or N-containing elements into the R1, R2, R3, or R4 groups can participate in film formation on the negative electrode side, generating an SEI film rich in LiF or Li3N inorganic components, thereby increasing the mechanical strength of the SEI film and, in turn, the stability of the SEI film on the negative electrode side. On the other hand, the introduction of metal ion additives into the electrolyte helps to synergize with the cyclic sulfate compounds, participate in the formation of inorganic films, and further form a stable SEI film, which can further prevent electron tunneling, reduce interfacial impedance, and significantly improve the battery's rate performance.
[0010] In any embodiment, R1, R2, R3, and R4 are each independently selected from the structure shown in Formula II, a hydrogen atom, a C 1- One of a C6 alkyl group, a halogen atom, a C1-C3 haloalkyl group, a C1-C3 alkoxy group and a cyano group.
[0011] R1, R2, R3, and R4 are each independently selected from the structure shown in Formula II, a hydrogen atom, a C 1- One of a C6 alkyl group, a halogen atom, a C1-C3 haloalkyl group, a C1-C3 alkoxy group and a cyano group is beneficial to the separation of R1, R2, R3 or R4 from the cyclic sulfate group during the battery charging process to form an organic film, thereby increasing the interface stability between the electrolyte and the negative electrode sheet and improving the rate performance of the battery.
[0012] In any embodiment, R1 is selected from hydrogen atom, C 1- C3 alkyl; R2 is selected from C 1- C3 alkyl, halogen atom, C1-C3 haloalkyl, cyano or the structure shown in formula II; R3 is selected from hydrogen atom, C 1- C3 alkyl; R4 is selected from C 1- C3 alkyl, halogen atom, C1-C3 alkoxy or the structure represented by formula II.
[0013] In any embodiment, R1 is selected from a hydrogen atom or a methyl group; R2 is selected from a methyl group, an ethyl group, a fluorine atom, a trifluoromethyl group, a cyano group or a structure shown in Formula II; R3 is selected from a hydrogen atom; R4 is selected from a methyl group, an ethyl group, a propyl group, a fluorine atom, an ethoxy group or a structure shown in Formula II.
[0014] In any embodiment, R1 and R3 are hydrogen atoms; R2 and R4 are methyl, ethyl, fluorine atoms or the structure shown in Formula II; or, R2 is a methyl or the structure shown in Formula II, and R4 is a methyl.
[0015] In any embodiment, R1 and R3 are hydrogen atoms; R2 and R4 are methyl groups or the structure shown in Formula II.
[0016] In any embodiment, R5 and R6 are each independently selected from hydrogen atom and C 1- One of the C3 alkyl groups.
[0017] In any embodiment, the cyclic sulfate compound is selected from one or more of the following compounds:
[0018] Adding the above-mentioned cyclic sulfate compounds to the electrolyte helps to form a SEI film in which organic and inorganic films are mixed with each other, forming a more stable interface and improving the rate performance of the battery.
[0019] In any embodiment, based on the total mass of the electrolyte, the mass content W of the cyclic sulfate compound satisfies: 0.001%≤W≤20%, and can be optionally 0.1% to 5%.
[0020] Controlling the mass content of the cyclic sulfate ester compound within an appropriate range can not only meet the demand for improving the battery rate performance, but also avoid or reduce the impact of an excessively high mass content of the cyclic sulfate ester compound on the ion transfer rate.
[0021] In any embodiment, the metal ion additive includes one or more of alkali metal ions, alkaline earth metal ions, and high-valent metal ions.
[0022] In any embodiment, the alkali metal ions include one or more of sodium ions, lithium ions, and potassium ions; and / or
[0023] Based on the total mass of the electrolyte, the mass content of the alkali metal ions is 30 ppm to 3000 ppm, and can be optionally 50 ppm to 2000 ppm.
[0024] The introduction of alkali metal ions into the electrolyte helps to form an inorganic SEI film with stronger electron blocking ability. By controlling the mass content of alkali metal ions, a stable SEI film can be formed, and the impact of the introduction of alkali metal ions on the electrolyte system can be avoided or reduced.
[0025] In any embodiment, the high-valent metal ions include one or more of aluminum ions and copper ions; and / or
[0026] Based on the total mass of the electrolyte, the mass content of the high-valent metal ions is 0.5 ppm to 300 ppm, and can be optionally 15 ppm to 200 ppm.
[0027] The introduction of high-valent metal ions into the electrolyte helps to form an inorganic SEI film with stronger electron blocking ability. By controlling the mass content of high-valent metal ions, a stable SEI film can be formed, and the impact of the introduction of high-valent metal ions on the electrolyte system can be avoided or reduced.
[0028] In any embodiment, the alkaline earth metal ions include one or more of magnesium ions and calcium ions; and / or
[0029] Based on the total mass of the electrolyte, the mass content of the alkaline earth metal ions is 0.5 ppm to 500 ppm, and can be optionally 13 ppm to 400 ppm.
[0030] The introduction of alkaline earth metal ions into the electrolyte helps to form an inorganic SEI film with stronger electron blocking ability. By controlling the mass content of alkaline earth metal ions, a stable SEI film can be formed, and the impact of the introduction of alkaline earth metal ions on the electrolyte system can be avoided or reduced.
[0031] In any embodiment, the electrolyte further comprises an electrolyte salt, and the electrolyte salt comprises a lithium salt or a sodium salt;
[0032] The lithium salt includes one or more of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorobis(oxalatophosphate), and lithium dioxalatoborate;
[0033] The sodium salt includes one or more of sodium hexafluorophosphate, sodium difluorooxalatoborate, sodium perchlorate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethanesulfonyl)imide, and sodium trifluoromethanesulfonate.
[0034] The above-mentioned lithium salt or sodium salt has good compatibility with the cyclic sulfate ester compound, and the introduction of an appropriate amount of the cyclic sulfate ester compound into the electrolyte will not affect the lithium salt or sodium salt.
[0035] A second aspect of the present application provides a secondary battery comprising a negative electrode plate and the electrolyte described in the first aspect.
[0036] In any embodiment, the secondary battery includes a sodium battery or a lithium battery.
[0037] In any embodiment, the negative electrode plate includes a negative electrode active material, and the negative electrode active material includes one or more of artificial graphite, natural graphite, hard carbon, soft carbon, mesophase carbon microbeads, carbon fibers, carbon nanotubes, elemental silicon, silicon oxides, silicon-carbon composites, silicon alloys, elemental tin, tin oxides, and titanium composite materials.
[0038] The above-mentioned negative electrode active materials all have excellent gram capacity and high specific surface area, which makes the battery have a high energy density.
[0039] In any embodiment, the active specific surface area A of the negative electrode plate and the mass content W of the cyclic sulfate compound satisfy: 0.0002 cm 2 / g≤W×A≤0.04cm 2 / g, optionally, 0.02cm 2 / g≤W×A≤0.1cm 2 / g.
[0040] The active specific surface area A of the negative electrode sheet and the mass content W of the cyclic sulfate compound satisfy a certain relationship, which can form a stable SEI film while taking into account the rate performance and cycle performance of the battery, and fully utilize the capacity of the battery.
[0041] In any embodiment, the active specific surface area A of the negative electrode sheet satisfies: A≤20cm 2 / g, optional 5cm 2 / g~15cm 2 / g.
[0042] Controlling the active specific surface area A of the negative electrode within an appropriate range can avoid or reduce the increase in battery polarization caused by an excessively small active specific surface area of the negative electrode, which affects the volatilization of the battery capacity, and the increase in interfacial side reactions caused by an excessively large active specific surface area of the negative electrode, which affects the battery's cycle performance and storage performance. Having an active specific surface area A within an appropriate range can balance the battery's cycle performance, storage performance, and capacity.
[0043] The third aspect of the present application provides an electric device, comprising the secondary battery of the second aspect of the present application BRIEF DESCRIPTION OF THE DRAWINGS
[0044] FIG1 is a schematic diagram of a secondary battery cell according to an embodiment of the present application;
[0045] FIG2 is an exploded view of a secondary battery cell according to an embodiment of the present application shown in FIG1 ;
[0046] FIG3 is a schematic diagram of a battery module according to an embodiment of the present application;
[0047] FIG4 is a schematic diagram of a battery pack according to an embodiment of the present application;
[0048] FIG5 is an exploded view of the battery pack according to an embodiment of the present application shown in FIG4 ;
[0049] FIG6 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.
[0050] Explanation of reference numerals: 1 battery pack; 2 upper case; 3 lower case; 4 battery module; 5 secondary battery cell; 51 housing; 52 electrode assembly; 53 cover plate. DETAILED DESCRIPTION
[0051] Below, the embodiments of the electrolyte, secondary battery and electrical device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0052] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0053] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0054] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0055] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0056] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0057] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0058] Currently, there are many problems with electrolytes. Taking lithium batteries as an example, electrolytes usually include ester solvents (such as vinylene carbonate). Ester solvents are prone to side reactions with lithium reaction interfaces, forming an SEI film rich in organic components such as alkyl lithium, resulting in increased impedance and affecting the power performance of the battery. At the same time, excessively high impedance may cause lithium plating at the negative electrode, further deteriorating the life of the battery cell. Therefore, it is necessary to design an electrolyte that can meet the application needs of the new generation of electrochemical systems.
[0059] [Electrolyte]
[0060] Based on this, the present application provides an electrolyte, which includes a cyclic sulfate compound shown in Formula I and a metal ion additive.
[0061] In formula I, R1, R2, R3, and R4 are each independently selected from the structure shown in formula II, a hydrogen atom, a C 1- One of a C6 alkyl group, a halogen atom, a C1-C3 haloalkyl group, a C1-C3 alkoxy group, a C1-C3 haloalkoxy group, a double bond, an ester group, a cyano group, and a sulfonic acid group, and R1, R2, R3, and R4 are not simultaneously selected from a hydrogen atom;
[0062] In formula II, R5 and R6 are each independently selected from hydrogen atom, C 1- One of a C6 alkyl group, a halogen atom, a C1-C3 haloalkyl group, a C1-C3 alkoxy group, a C1-C3 haloalkoxy group, a double bond, an ester group, a cyano group and a sulfonic acid group, and a wavy line indicates a bonding position.
[0063] In this article, the term “C 1- "C6 alkyl" refers to a straight or branched hydrocarbon chain radical consisting solely of carbon and hydrogen atoms, with no unsaturation present, having from one to six carbon atoms, and attached to the remainder of the molecule by a single bond. Examples of C1-C6 alkyl groups include, but are not limited to, methyl, ethyl, n-propyl, 1-methylethyl (isopropyl), n-butyl, n-pentyl, and n-hexyl.
[0064] As used herein, the term "cyclic sulfate compound" refers to a cyclic compound containing a sulfate group having two oxygen atoms and a sulfur atom in the sulfate group as ring atoms of a five-membered ring structure.
[0065] As used herein, the term "metal ion additive" refers to a salt added to the electrolyte at a concentration of 5% or less, consisting entirely of metal cations and anions, and being liquid at or near room temperature. Metal cations include, but are not limited to, sodium, lithium, potassium, aluminum, copper, magnesium, or calcium ions. Room temperature refers to 25°C ± 5°C.
[0066] In this article, the term “C 1- "C3 alkyl" refers to a straight or branched hydrocarbon chain radical consisting solely of carbon and hydrogen atoms, with no unsaturation present, having from one to three carbon atoms, and attached to the remainder of the molecule by a single bond. 1- Examples of C3 alkyl groups include, but are not limited to, methyl, ethyl, n-propyl, and 1-methylethyl (isopropyl).
[0067] As used herein, the term "halogen atom" refers to elements of Group VIIA of the periodic system, including but not limited to: F, Cl, Br, I, and At.
[0068] In this context, the term "C1-C3 haloalkyl" refers to 1- At least one hydrogen atom in the C3 alkyl group is substituted by a halogen atom, including but not limited to chloroform, difluoroethylene, and 3-fluoropropylene.
[0069] In this context, the term "C1-C3 alkoxy" refers to a 1- The C3 alkyl group is composed of an oxygen atom, including but not limited to methoxy (CH3O-), ethoxy (C2H5O-), and propoxy (C3H7O-).
[0070] In this context, the term "C1-C3 haloalkoxy" refers to 1- At least one hydrogen atom in the C3 alkoxy group is substituted by a halogen atom, including but not limited to: 1,1,1,2,2-pentafluoro-2-(2,2,2-trifluoroethoxy)ethane, 1-(2,2-difluoroethoxy)-2-(2,2,2-trifluoroethoxy)ethane, and 1,2-bis(2-fluoroethoxy)ethane.
[0071] As used herein, the term "double bond" refers to a multiple bond between two atoms in a compound molecule formed by two shared electron pairs, ie, a carbon-carbon double bond.
[0072] As used herein, the term "ester group" refers to -COOR 10 Group, where R 10 Selected from substituted or unsubstituted C 1-5 In this article, the term "C 1- "C5 alkyl" refers to a straight or branched hydrocarbon chain radical consisting solely of carbon and hydrogen atoms, with no unsaturation present in the radical, having from one to five carbon atoms, and attached to the remainder of the molecule by a single bond.
[0073] As used herein, the term "cyano" refers to a -CN group.
[0074] As used herein, the term "sulfonic acid" refers to a -SO3H group.
[0075] As used herein, the term "bonding position" refers to the position at which the structure represented by Formula II and the structure represented by Formula I form a bond.
[0076] On the one hand, the introduction of cyclic sulfate compounds into the electrolyte facilitates the formation of a stable SEI film. During battery charging, the cyclic sulfate groups help form a sulfite-based inorganic film between the electrolyte and the negative electrode, while the R1, R2, R3, or R4 groups help form a resilient organic film between the electrolyte and the negative electrode. For example, by introducing alkyl / alkoxy groups into the R1, R2, R3, or R4 groups, a resilient SEI film with longer organic chains can be generated on the negative electrode side to cope with the volume changes on the negative electrode side during cycling, thereby avoiding or reducing SEI film damage and improving SEI film stability. Furthermore, the introduction of F- or N-containing elements into the R1, R2, R3, or R4 groups can participate in film formation on the negative electrode side, generating an SEI film rich in LiF or Li3N inorganic components, thereby increasing the mechanical strength of the SEI film and, in turn, the stability of the SEI film on the negative electrode side. On the other hand, the introduction of metal ion additives into the electrolyte helps to synergize with the cyclic sulfate compounds, participate in the formation of inorganic films, and further form a stable SEI film, which can further prevent electron tunneling, reduce interfacial impedance, and significantly improve the battery's rate performance.
[0077] On the other hand, the introduction of metal ion additives into the electrolyte helps to synergize with the cyclic sulfate compounds, participate in the formation of inorganic films, and further form a stable SEI film, which can further prevent electron tunneling, reduce interfacial impedance, and significantly improve the battery's rate performance.
[0078] In some embodiments, R1, R2, R3, and R4 are each independently selected from the structure shown in Formula II, a hydrogen atom, a C 1- One of a C6 alkyl group, a halogen atom, a C1-C3 haloalkyl group, a C1-C3 alkoxy group and a cyano group.
[0079] R1, R2, R3, and R4 are each independently selected from the structure shown in Formula II, a hydrogen atom, a C 1- One of the C6 alkyl group, the halogen atom, the C1-C3 haloalkyl group, the C1-C3 alkoxy group and the cyano group is beneficial to the separation of R1, R2, R3 or R4 from the cyclic sulfate group during the battery charging process to form an organic film, thereby increasing the interface stability between the electrolyte and the negative electrode sheet and improving the rate performance of the battery.
[0080] In some embodiments, R1 is selected from hydrogen atom, C 1- C3 alkyl; R2 is selected from C 1- C3 alkyl, halogen atom, C1-C3 haloalkyl, cyano or the structure shown in formula II; R3 is selected from hydrogen atom, C 1- C3 alkyl; R4 is selected from C 1- C3 alkyl, halogen atom, C1-C3 alkoxy or the structure represented by formula II.
[0081] In some embodiments, R1 is selected from a hydrogen atom or a methyl group; R2 is selected from a methyl group, an ethyl group, a fluorine atom, a trifluoromethyl group, a cyano group or a structure shown in Formula II; R3 is selected from a hydrogen atom; R4 is selected from a methyl group, an ethyl group, a propyl group, a fluorine atom, an ethoxy group or a structure shown in Formula II.
[0082] In some embodiments, R1 and R3 are hydrogen atoms; R2 and R4 are methyl, ethyl, fluorine atoms or the structure shown in Formula II; or, R2 is a methyl or the structure shown in Formula II, and R4 is a methyl.
[0083] In some embodiments, R1 and R3 are hydrogen atoms; R2 and R4 are methyl groups or the structure shown in Formula II.
[0084] In some embodiments, R5 and R6 are each independently selected from hydrogen atom and C 1- One of the C3 alkyl groups.
[0085] In some embodiments, the cyclic sulfate compound is selected from one or more of the following compounds:
[0086] Adding the above-mentioned cyclic sulfate compounds to the electrolyte helps to form a SEI film in which organic and inorganic films are mixed with each other, forming a more stable interface and improving the rate performance of the battery.
[0087] In some embodiments, based on the total mass of the electrolyte, the mass content W of the cyclic sulfate ester compound satisfies: 0.001%≤W≤20%, and may be 0.1% to 5%.
[0088] In some embodiments, based on the total mass of the electrolyte, the mass content W of the cyclic sulfate compound can be selected to be 0.001%, 0.005%, 0.01%, 0.05%, 0.1%, 0.2%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, 2%, 4%, 5%, 6%, 8%, 10%, 12%, 14%, 15%, 16%, 18%, 20%, or a value in the range consisting of any two of the above points.
[0089] Controlling the mass content of the cyclic sulfate compound within an appropriate range can not only meet the demand for improving battery rate performance, but also reduce or minimize the impact of excessively high mass content of the cyclic sulfate compound on the ion transfer rate.
[0090] In some embodiments, the metal ion additive includes one or more of alkali metal ions, alkaline earth metal ions, and high-valent metal ions.
[0091] In some embodiments, the alkali metal ions include one or more of sodium ions, lithium ions, and potassium ions.
[0092] In some embodiments, based on the total mass of the electrolyte, the mass content of the alkali metal ions is 30 ppm to 3000 ppm, optionally 50 ppm to 2000 ppm.
[0093] In some embodiments, based on the total mass of the electrolyte, the mass content of alkali metal ions can be selected as 30ppm, 50ppm, 100ppm, 200ppm, 400ppm, 500ppm, 600ppm, 800ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, or a value in the range consisting of any two of the above points.
[0094] It can be understood that the alkali metal ions in the metal ion additive can participate in the formation of the SEI film and consume part of the alkali metal ions, resulting in a decrease in the mass content of alkali metal ions in the electrolyte. For example, the mass content of alkali metal ions in the electrolyte is 30 ppm. Therefore, based on the total mass of the electrolyte, the mass content of alkali metal ions is 30 ppm to 3000 ppm, which is the range protected in the embodiments of the present application.
[0095] The introduction of alkali metal ions into the electrolyte helps to form an inorganic SEI film with stronger electron blocking ability. By controlling the mass content of alkali metal ions, a stable SEI film can be formed, and the impact of the introduction of alkali metal ions on the electrolyte system can be avoided or reduced.
[0096] In some embodiments, the high-valent metal ions include one or more of aluminum ions and copper ions.
[0097] In some embodiments, based on the total mass of the electrolyte, the mass content of the high-valent metal ions is 0.5 ppm to 300 ppm, and optionally 15 ppm to 200 ppm.
[0098] In some embodiments, based on the total mass of the electrolyte, the mass content of the high-valent metal ions can be selected as 0.5ppm, 1ppm, 5ppm, 10ppm, 15ppm, 20ppm, 30ppm, 40ppm, 50ppm, 60ppm, 70ppm, 80ppm, 90ppm, 100ppm, 150ppm, 200ppm, 250ppm, 300ppm, or a value in the range consisting of any two of the above points.
[0099] It can be understood that the high-valent metal ions in the metal ion additive can participate in the formation of the SEI film and consume part of the high-valent metal ions, resulting in a decrease in the mass content of high-valent metal ions in the electrolyte. For example, the mass content of high-valent metal ions in the electrolyte is 0.5 ppm. Therefore, based on the total mass of the electrolyte, the mass content of high-valent metal ions is 0.5 ppm to 300 ppm, which is the range protected in the embodiments of the present application.
[0100] The introduction of high-valent metal ions into the electrolyte helps to form an inorganic SEI film with stronger electron blocking ability. By controlling the mass content of high-valent metal ions, a stable SEI film can be formed and the impact of the introduction of high-valent metal ions on the electrolyte system can be reduced or minimized.
[0101] In some embodiments, the alkaline earth metal ions include one or more of magnesium ions and calcium ions.
[0102] In some embodiments, based on the total mass of the electrolyte, the mass content of the alkaline earth metal ions is 0.5 ppm to 500 ppm, and optionally 13 ppm to 400 ppm.
[0103] In some embodiments, based on the total mass of the electrolyte, the mass content of alkaline earth metal ions can be selected as 0.5ppm, 1ppm, 5ppm, 10ppm, 13ppm, 15ppm, 20ppm, 30ppm, 40ppm, 50ppm, 60ppm, 70ppm, 80ppm, 90ppm, 100ppm, 150ppm, 200ppm, 250ppm, 300ppm, 350ppm, 400ppm, 450ppm, 500ppm, or a value in the range consisting of any two of the above points.
[0104] It can be understood that the alkaline earth metal ions in the metal ion additive can participate in the formation of the SEI film and consume part of the alkaline earth metal ions, resulting in a decrease in the mass content of alkaline earth metal ions in the electrolyte. For example, the mass content of alkaline earth metal ions in the electrolyte is 0.5 ppm. Therefore, based on the total mass of the electrolyte, the mass content of alkaline earth metal ions is 0.5 ppm to 500 ppm, which is the range protected in the embodiments of the present application.
[0105] The introduction of alkaline earth metal ions into the electrolyte helps to form an inorganic SEI film with stronger electron blocking ability. By controlling the mass content of alkaline earth metal ions, a stable SEI film can be formed and the impact of the introduction of alkaline earth metal ions on the electrolyte system can be reduced or minimized.
[0106] The metal ions can be introduced into the electrolyte by adding a salt containing the selected metal ion, which can be a hexafluorophosphate, such as sodium hexafluorophosphate.
[0107] The mass content of the metal ions in the metal ion additive in the electrolyte can be detected using instruments and methods known in the art, including but not limited to, using an ICP (Inductive Coupled Plasma Emission Spectrometer) inductively coupled plasma spectrometer, and detecting according to the standard operating procedures recommended by the instrument manufacturer or industry specifications in this field.
[0108] In some embodiments, the electrolyte further comprises an electrolyte salt, and the electrolyte salt comprises a lithium salt or a sodium salt;
[0109] The lithium salt includes one or more of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium difluorobis(oxalatophosphate) (LiDFOP), and lithium dioxalatoborate (LiBOB);
[0110] The sodium salt includes one or more of sodium hexafluorophosphate (NaPF6), sodium difluorooxalatoborate (NaDFOB), sodium perchlorate (NaClO4), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), and sodium trifluoromethanesulfonate (NaOTf).
[0111] In some embodiments, the concentration of the electrolyte salt is 0.1 mol / L to 5 mol / L, and can be 0.7 mol / L to 1.2 mol / L. In some embodiments, the concentration of the electrolyte salt can be 0.1 mol / L, 0.2 mol / L, 0.4 mol / L, 0.5 mol / L, 0.7 mol / L, 0.8 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L, 4 mol / L, 5.5 mol / L, 5 mol / L, or a value in a range consisting of any two of the above.
[0112] The above-mentioned lithium salt or sodium salt has good compatibility with the cyclic sulfate ester compound, and the introduction of an appropriate amount of the cyclic sulfate ester compound into the electrolyte will not affect the lithium salt or sodium salt.
[0113] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.
[0114] [Positive electrode]
[0115] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material, a conductive agent and a binder.
[0116] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector.
[0117] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0118] In some embodiments, the positive electrode active material may adopt the positive electrode active material for batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 ), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 ), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 ), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 ), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05O2) and its modified compounds. Examples of olivine-structured lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0119] In some embodiments, the conductive agent may be a conductive agent known in the art for use in batteries. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0120] In some embodiments, the binder may be a binder known in the art for use in batteries. For example, the binder may include polyvinylidene fluoride.
[0121] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0122] [Negative electrode]
[0123] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0124] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0125] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0126] In some embodiments, the negative electrode plate includes a negative electrode active material, and the negative electrode active material includes one or more of artificial graphite, natural graphite, hard carbon, soft carbon, mesophase carbon microbeads, carbon fibers, carbon nanotubes, elemental silicon, silicon oxides, silicon-carbon composites, silicon alloys, elemental tin, tin oxides, and titanium composites.
[0127] In some embodiments, the titanium composite material includes lithium titanate.
[0128] The above-mentioned negative electrode active materials all have excellent gram capacity and high specific surface area, which makes the battery have a high energy density.
[0129] In some embodiments, the active specific surface area A of the negative electrode plate and the mass content W of the cyclic sulfate compound satisfy the following conditions: 0.0002 cm 2 / g≤W×A≤0.04cm 2 / g, optionally, 0.02cm 2 / g≤W×A≤0.1cm 2 / g.
[0130] In this article, the term "active surface area" refers to the ratio of the active surface area of the negative electrode to its mass, and can be used to reflect the number of active sites on the negative electrode during charge and discharge. The larger the active surface area of the negative electrode, the more active sites it contains.
[0131] In this article, the active specific surface area of the negative electrode plate can be tested by any known method. As an example, the active specific surface area of the negative electrode plate is calculated according to the Randles-Sevcik equation in combination with the mass of the negative electrode plate. With the negative electrode plate as the cathode, the metal lithium plate as the anode, ferrocene at a concentration of 50mmol / L is added to the electrolyte (the same electrolyte used in the preparation method of the battery), and then assembled into a button half-cell. Take 4 parallel samples and scan them at scan rates v of 0.1mV / s, 0.3mV / s, 0.5mV / s, and 1mV / s, respectively, to obtain cyclic voltammetry curves at different scan rates, and use EC-Lab software to extract the peak current ip of the cyclic voltammetry curve. With the square root of the scan rate v as the horizontal coordinate and the peak current ip as the vertical coordinate, make a linear graph of the cyclic voltammetry curve ip and the square root of the scan rate v to obtain its slope K.
[0132] According to the Randles-Sevcik equation, the slope is: n represents the number of electron transfers, which is related to the type of probe molecule and is taken as 1; c represents the concentration of ferrocene and is taken as 50 mmol / L; D is the diffusion coefficient of ferrocene and is taken as 2.1×10 -6 cm 2 / s; then the active surface area of the negative electrode A=K / (2.69×10 5 ×n2 / 3 cD 1 / 2 ), the ratio of the active surface area A of the negative electrode sheet to the weight m of the negative electrode sheet is the active specific surface area of the negative electrode sheet.
[0133] In some embodiments, the product of the active specific surface area A of the negative electrode plate and the mass content W of the cyclic sulfate compound can be selected to be 0.0002 cm 2 / g, 0.0005cm 2 / g, 0.002cm 2 / g, 0.005cm 2 / g, 0.02cm 2 / g, 0.022cm 2 / g, 0.024cm 2 / g, 0.025cm 2 / g, 0.026cm 2 / g, 0.028cm 2 / g, 0.03cm 2 / g, 0.032cm 2 / g, 0.034cm 2 / g, 0.035cm 2 / g, 0.036cm 2 / g, 0.038cm 2 / g, 0.04cm 2 / g, or a value within the range consisting of any two of the above points.
[0134] The active specific surface area A of the negative electrode sheet and the mass content W of the cyclic sulfate compound satisfy the above relationship, which can form a stable SEI film while taking into account the rate performance and cycle performance of the battery, and fully utilize the capacity of the battery.
[0135] In some embodiments, the active specific surface area A of the negative electrode sheet satisfies: A≤20cm 2 / g, optional 5cm 2 / g~15cm 2 / g.
[0136] In some embodiments, the active specific surface area A of the negative electrode sheet can be selected to be 1 cm 2 / g, 2cm 2 / g, 4cm 2 / g, 5cm 2 / g, 6cm 2 / g、8cm 2 / g, 10cm 2 / g, 11cm 2 / g, 12cm 2 / g, 13cm 2 / g, 14cm 2 / g, 15cm 2 / g, or a value within the range consisting of any two of the above points.
[0137] Controlling the active specific surface area A of the negative electrode within an appropriate range can avoid or reduce the increase in battery polarization caused by an excessively small active specific surface area of the negative electrode, which affects the volatilization of the battery capacity, and the increase in interfacial side reactions caused by an excessively large active specific surface area of the negative electrode, which affects the battery's cycle performance and storage performance. Having an active specific surface area A within an appropriate range can balance the battery's cycle performance, storage performance, and capacity.
[0138] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0139] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0140] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0141] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0142] [Isolation film]
[0143] In some embodiments, the secondary battery further includes a separator. In the present application, the separator can be any well-known porous structure separator with good chemical stability and mechanical stability.
[0144] In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer can be the same or different.
[0145] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.
[0146] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.
[0147] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the secondary battery can be a soft shell, such as a pouch-type soft shell. The soft shell can be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0148] [Secondary battery]
[0149] In this application, the shape of a secondary battery includes but is not limited to cylindrical, square, or any other shape. For example, FIG1 shows a secondary battery 5 having a square structure as an example. The secondary battery can also be a sodium ion secondary battery, a sodium ion secondary battery, a magnesium ion secondary battery, or a potassium ion secondary battery.
[0150] In some embodiments, the secondary battery includes the electrolyte provided in this application. In some embodiments, the secondary battery includes the negative electrode provided in this application.
[0151] In some embodiments, referring to FIG2 , the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0152] [Battery Module]
[0153] In some embodiments, secondary batteries can be assembled into a battery module. The number of secondary batteries contained in the battery module can be one or more. The specific number can be selected by those skilled in the art according to the application and capacity of the battery module.
[0154] Figure 3 shows an example battery module 4. Referring to Figure 3 , within the battery module 4, multiple secondary batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple secondary batteries 5 may be secured together using fasteners.
[0155] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0156] [Battery Pack]
[0157] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art based on the application and capacity of the battery pack.
[0158] Figures 4 and 5 illustrate an example battery pack 1. Referring to Figures 4 and 5 , the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 can be placed over the lower case 3 to form an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0159] [Electrical devices]
[0160] In one embodiment of the present application, an electric device is provided, comprising at least one of a secondary battery according to any embodiment, a battery module according to any embodiment, or a battery pack according to any embodiment.
[0161] The electrical device includes at least one of the secondary battery, battery module, or battery pack provided in this application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0162] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.
[0163] Figure 6 shows an example of an electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.
[0164] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.
[0165] Example
[0166] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0167] 1. Preparation method
[0168] Example 1
[0169] 1) Preparation of cyclic sulfate compounds
[0170] 364.3 g (2 mol) of galactitol was added to a 4 L three-necked flask and stirred. 784.5 g (6.6 mol) of thionyl chloride was added dropwise to the three-necked flask. The temperature was controlled at about 15 ° C during the addition. After the addition was completed, the reaction was kept at 45 ° C for 4 hours. A large amount of pasty solids precipitated from the reaction solution. After cooling, 1 L of deionized water was slowly added dropwise. The reaction system was quickly stirred and dispersed. The filtered solid was washed with deionized water several times until the pH was neutral. The filter cake was dried under reduced pressure at 60 ° C to obtain an intermediate product.
[0171] To a 4L three-necked flask was added 140g (0.4mol) of the above intermediate product, 1000mL of acetonitrile was added, 110mg of ruthenium trichloride trihydrate catalyst was added, and after nitrogen replacement of the system, the system was cooled to 20 ° C., stirring was started, and 1500g of 20% sodium hypochlorite aqueous solution was added dropwise within 1h, and the reaction temperature was controlled at 15 ° C. After the addition was complete, stirred at 15 ° C for 10min, separated, and the organic phase was quenched with sodium sulfite aqueous solution until the starch potassium iodide test paper did not turn blue; the liquid was separated again, the organic layer was concentrated, and acetonitrile was crystallized to obtain compound Ι-1.
[0172] 2) Preparation of the Positive Electrode: 2.5wt% polyvinylidene fluoride binder was fully dissolved in N-methylpyrrolidone (NMP). 2.0wt% Super P, 1.0wt% carbon nanotubes, and 94.5wt% lithium iron phosphate (LiFePO4), the positive electrode active material, were added and mixed thoroughly to form a positive electrode slurry. The slurry was evenly coated on the surface of the current collector aluminum foil and then transferred to a vacuum drying oven for complete drying. The dried electrode was then roll-pressed and punched to obtain the positive electrode sheet.
[0173] 3) Preparation of negative electrode sheet
[0174] The active material artificial graphite, conductive agent carbon black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) are dissolved in deionized water at a weight ratio of 96.2:0.8:0.8:1.2, and mixed evenly to prepare a negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil once or multiple times, and then dried, cold pressed, and cut to obtain a negative electrode sheet. The active specific surface area of the negative electrode sheet is 8cm 2 / g.
[0175] 4) Electrolyte
[0176] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), the lithium salt lithium hexafluorophosphate LiPF6, the cyclic sulfate compound with the structure shown in Formula I-1 and the metal ion additive sodium hexafluorophosphate NaPF6 were dissolved in a mixed system of organic solvent ethylene carbonate / dimethyl carbonate / ethyl methyl carbonate (EC:DMC:EMC mass ratio is 1:1:1) and stirred evenly to obtain an electrolyte with a lithium salt concentration of 1 mol / L.
[0177] 5) Isolation film
[0178] Polypropylene film is used as the isolation film.
[0179] 6) Preparation of batteries
[0180] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is placed between the positive and negative electrode sheets to play an isolating role, and then wound to obtain an electrode assembly; the electrode assembly is placed in a battery case, and after drying, the electrolyte is injected, and then the process is sequentially carried out through the steps of standing, hot and cold pressing, formation, shaping, and capacity testing to obtain the lithium battery product of Example 1.
[0181] Example 2
[0182] The preparation method of the battery of Example 2 is similar to that of the battery of Example 1, but the preparation method of the cyclic sulfate ester compound is adjusted. The specific preparation method is as follows:
[0183] 392.4 g (2 mol) of solid 1,2,3,4,5.6-heptanhexaol was added to a 4 L three-necked flask and stirred. 784.5 g (6.6 mol) of thionyl chloride was added dropwise to the three-necked flask. The temperature was controlled at about 15 ° C during the addition. After the addition was completed, the reaction was kept at 45 ° C for 4 hours. A large amount of pasty solids precipitated from the reaction solution. After cooling, 1 L of deionized water was slowly added dropwise. The reaction system was quickly stirred to break up. The filtered solid was washed with deionized water several times to neutral pH. The filter cake was dried under reduced pressure at 60 ° C to obtain an intermediate product.
[0184] To a 4L three-necked flask was added 140g (0.4mol) of intermediate 1, 1000mL of acetonitrile, 110mg of ruthenium trichloride trihydrate catalyst, and after nitrogen replacement of the system, the system was cooled to 20 ° C., stirring was started, and 1500g of 20% sodium hypochlorite aqueous solution was added dropwise within 1h, and the reaction temperature was controlled at 15 ° C. After the addition was complete, the mixture was stirred at 15 ° C. for 10min, separated, and the organic phase was quenched with sodium sulfite aqueous solution until the starch potassium iodide test paper did not turn blue; the liquid was separated again, the organic layer was concentrated, and acetonitrile was crystallized to obtain compound Ι-2.
[0185] Example 3
[0186] The preparation method of the battery of Example 3 is similar to that of the battery of Example 1, but the preparation method of the cyclic sulfate ester compound is adjusted. The specific preparation method is as follows:
[0187] 484 g (2 mol) of solid octitol was added to a 2 L three-necked flask and stirred. 1046 g (8.8 mol) of thionyl chloride was added dropwise to the three-necked flask. The temperature was controlled at about 15 ° C during the addition. After the addition was completed, the reaction was kept at 45 ° C for 4 hours. A large amount of pasty solids precipitated from the reaction solution. After cooling, 1 L of deionized water was slowly added dropwise. The reaction system was quickly stirred and dispersed. The filtered solid was washed with deionized water several times until the pH was neutral. The filter cake was dried under reduced pressure at 60 ° C to obtain an intermediate product.
[0188] To a 4L three-necked flask was added 183.2g (0.4mol) of the intermediate product, 1000mL of acetonitrile was added, 150mg of ruthenium trichloride trihydrate catalyst was added, and after nitrogen substitution, the system was cooled to 20°C, stirring was started, and 2000g of 20% sodium hypochlorite aqueous solution was added dropwise within 1h, and the reaction temperature was controlled at 10-20°C; after the addition was complete, stirred at 10-20°C for 10min, separated, and the organic phase was quenched with sodium sulfite aqueous solution until the starch potassium iodide test paper did not turn blue; the liquid was separated again, the organic layer was concentrated, and acetonitrile was crystallized to obtain compound Ι-5.
[0189] Example 4
[0190] The preparation method of the battery of Example 4 is similar to that of the battery of Example 1, but the preparation method of the cyclic sulfate ester compound is adjusted. The specific preparation method is as follows:
[0191] 300 g (2 mol) of solid 1,6-dideoxygalactitol was added to a 3 L three-necked flask and stirred. 523 g (4.4 mol) of thionyl chloride was added dropwise to the three-necked flask. The temperature was controlled at about 15 ° C during the addition. After the addition was completed, the reaction was kept at 45 ° C for 4 hours. A large amount of pasty solids precipitated from the reaction solution. After cooling, 1 L of deionized water was slowly added dropwise. The reaction system was quickly stirred to break up. The filtered solid was washed with deionized water several times until the pH was neutral. The filter cake was dried under reduced pressure at 60 ° C to obtain an intermediate product.
[0192] To a 3L three-necked flask was added 184.2 g (0.8 mol) of the above intermediate product, 1000 mL of acetonitrile, 80 mg of ruthenium trichloride trihydrate catalyst, and after nitrogen substitution, the system was cooled to 20°C and stirred. Within 1 hour, 2000 g of a 20% aqueous sodium hypochlorite solution was added dropwise, and the reaction temperature was controlled at 15°C. After the addition was complete, the mixture was stirred at 15°C for 10 minutes, separated, and the organic phase was quenched with an aqueous sodium sulfite solution until the starch potassium iodide test paper did not turn blue. The liquid was separated again, the organic layer was concentrated, and crystallized from acetonitrile to obtain a white powder solid, which was the above-mentioned compound I-6. 1H-NMR, CD3CN, δppm 5.42-5.39 (m, 2H), 5.36-5.34 (m, 2H), 1.67-1.65 (d, 6H).
[0193] Example 5
[0194] The preparation method of the battery of Example 5 is similar to that of the battery of Example 1, but the preparation method of the cyclic sulfate ester compound is adjusted. The specific preparation method is as follows:
[0195] 356.5 g (2 mol) of solid 3,4,5,6-octanetrol was added to a 2 L three-necked flask and stirred. 523 g (4.4 mol) of thionyl chloride was added dropwise to the three-necked flask. The temperature was controlled at about 15 ° C during the addition. After the addition was completed, the reaction was kept at 45 ° C for 4 hours. A large amount of pasty solid precipitated from the reaction solution. After cooling, 1 L of deionized water was slowly added dropwise. The reaction system was quickly stirred and dispersed. The filtered solid was washed with deionized water several times until the pH was neutral. The filter cake was dried under reduced pressure at 60 ° C to obtain an intermediate product.
[0196] To a 3L three-necked flask was added 216.2g (0.8mol) of the above intermediate product, 1000mL of acetonitrile was added, 80mg of ruthenium trichloride trihydrate catalyst was added, and after nitrogen replacement of the system, the system was cooled to 20 ° C., stirring was started, and 2000g of 20% sodium hypochlorite aqueous solution was added dropwise within 1h, and the reaction temperature was controlled at 15 ° C.; after the addition was completed, stirred at 15 ° C for 10min, separated, and the organic phase was quenched with sodium sulfite aqueous solution until the starch potassium iodide paper did not turn blue; the liquid was separated again, the organic layer was concentrated, and acetonitrile was crystallized to obtain compound Ι-7.
[0197] Example 6
[0198] The preparation method of the battery of Example 6 is similar to that of the battery of Example 1, but the preparation method of the cyclic sulfate ester compound is adjusted. The specific preparation method is as follows:
[0199] 328.4 g (2 mol) of solid 2,3,4,5-heptetrol was added to a 2 L three-necked flask and stirred. 523 g (4.4 mol) of thionyl chloride was added dropwise to the three-necked flask. The temperature was controlled at about 15 ° C during the addition. After the addition was completed, the reaction was kept at 45 ° C for 4 hours. A large amount of pasty solids precipitated from the reaction solution. After cooling, 1 L of deionized water was slowly added dropwise. The reaction system was quickly stirred and dispersed. The filtered solid was washed with deionized water several times until the pH was neutral. The filter cake was dried under reduced pressure at 60 ° C to obtain an intermediate product.
[0200] To a 3L three-necked flask, 205g (0.8mol) of the above intermediate product was added, 1000mL of acetonitrile was added, and the mixture was stirred until the solid was completely dissolved. 80mg of ruthenium trichloride trihydrate catalyst was added. After nitrogen displacement of the system, the system was cooled to 20°C, stirring was started, and 2000g of 20% aqueous sodium hypochlorite solution was added dropwise within 1h, and the reaction temperature was controlled at 10-20°C; after the addition was complete, the mixture was stirred at 10-20°C for 10min, separated, and the organic phase was quenched with sodium sulfite aqueous solution until the starch potassium iodide test paper did not turn blue; the liquid was separated again, the organic layer was concentrated, and the acetonitrile crystals were obtained to obtain compound I-8.
[0201] Examples 7 to 29
[0202] The batteries of Examples 7 to 29 were prepared similarly to the battery of Example 4, except that the mass content of the cyclic sulfate compound, the type and mass content of the metal ion, or the type of the negative electrode active material were adjusted. Specific parameters are shown in Table 1.
[0203] Example 30
[0204] 1) Preparation of cyclic sulfate compounds
[0205] 364.3 g (2 mol) of galactitol was added to a 4 L three-necked flask and stirred. 784.5 g (6.6 mol) of thionyl chloride was added dropwise to the three-necked flask. The temperature was controlled at about 15 ° C during the addition. After the addition was completed, the reaction was kept at 45 ° C for 4 hours. A large amount of pasty solids precipitated from the reaction solution. After cooling, 1 L of deionized water was slowly added dropwise. The reaction system was quickly stirred and dispersed. The filtered solid was washed with deionized water several times until the pH was neutral. The filter cake was dried under reduced pressure at 60 ° C to obtain an intermediate product.
[0206] To a 4L three-necked flask was added 140g (0.4mol) of the above intermediate product, 1000mL of acetonitrile was added, 110mg of ruthenium trichloride trihydrate catalyst was added, and after nitrogen replacement of the system, the system was cooled to 20 ° C., stirring was started, and 1500g of 20% sodium hypochlorite aqueous solution was added dropwise within 1h, and the reaction temperature was controlled at 15 ° C. After the addition was complete, stirred at 15 ° C for 10min, separated, and the organic phase was quenched with sodium sulfite aqueous solution until the starch potassium iodide test paper did not turn blue; the liquid was separated again, the organic layer was concentrated, and acetonitrile was crystallized to obtain compound Ι-1.
[0207] 2) Preparation of positive electrode sheet
[0208] The positive electrode active material, NaFePO4, the conductive agent, acetylene black, and the binder, polyvinylidene fluoride (PVDF), were thoroughly stirred and mixed in an N-methylpyrrolidone solvent system at a mass ratio of 80:10:10 to obtain a positive electrode slurry. The slurry was evenly coated on the surface of the current collector aluminum foil and then transferred to a vacuum drying oven for complete drying. The dried electrode sheet was then roll-pressed and punched to obtain the positive electrode sheet.
[0209] 3) Preparation of negative electrode sheet
[0210] The negative electrode active material hard carbon, conductive agent acetylene black, and binder polyacrylic acid are fully stirred in a deionized water solvent system at a mass ratio of 88:2:10, and mixed evenly to prepare a negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil once or multiple times, and then dried, cold pressed, and cut to obtain a negative electrode sheet. The active specific surface area of the negative electrode sheet is 8cm 2 / g.
[0211] 4) Electrolyte
[0212] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), sodium salt sodium hexafluorophosphate NaPF6, a cyclic sulfate compound with the structure shown in Formula I-1, and a metal ion additive lithium hexafluorophosphate LiPF6 were dissolved in a mixed system of organic solvent ethylene carbonate / dimethyl carbonate / ethyl methyl carbonate (EC:DMC:EMC mass ratio is 1:1:1), stirred evenly, and an electrolyte with a sodium salt concentration of 1 mol / L was obtained.
[0213] 5) Isolation film
[0214] Polypropylene film is used as the isolation film.
[0215] 6) Preparation of batteries
[0216] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator positioned between the positive and negative electrode sheets to provide insulation. The electrode assembly is then wound to form an electrode. The electrode assembly is placed in a battery casing, dried, and then injected with electrolyte. The battery is then subjected to a series of steps, including resting, hot and cold pressing, formation, shaping, and capacity testing, to obtain the sodium battery product of Example 33.
[0217] Examples 31 to 41
[0218] The batteries of Examples 31 to 41 were prepared similarly to the battery of Example 30, except that the type and mass content of the cyclic sulfate compound and the type of metal ion were adjusted. Specific parameters are shown in Table 1.
[0219] Examples 42 to 44
[0220] The batteries of Examples 42 to 44 were prepared in a similar manner to that of Example 4, except that the active specific surface area of the negative electrode was adjusted. Specific parameters are shown in Table 1.
[0221] Comparative Example 1
[0222] The battery of Comparative Example 1 was prepared in a similar manner to that of Example 1, except that the electrolyte did not contain the metal ion additive. Specific parameters are shown in Table 1.
[0223] Comparative Example 2
[0224] The battery of Comparative Example 2 was prepared similarly to the battery of Example 33, except that the electrolyte did not contain the metal ion additive. Specific parameters are shown in Table 1.
[0225] Comparative Example 3
[0226] The battery of Comparative Example 3 was prepared in a similar manner to that of Example 1, except that the electrolyte did not contain the cyclic sulfate compound. Specific parameters are shown in Table 1.
[0227] Comparative Example 4
[0228] The battery of Comparative Example 4 was prepared in a similar manner to the battery of Example 33, except that the electrolyte did not contain the cyclic sulfate compound. Specific parameters are shown in Table 1.
[0229] Comparative Example 5
[0230] The battery of Comparative Example 5 was prepared using a similar method to that of Example 1, except that the sulfate ester compound was prepared using the commercial compound vinyl disulfate (CAS No. 1431298-10-0, commercially available). The structural formula of vinyl disulfate is shown in Formula III. Specific parameters are shown in Table 1.
[0231] Comparative Example 6
[0232] The battery of Comparative Example 6 was prepared in a similar manner to the battery of Comparative Example 5, except that the type of electrolyte salt in the electrolyte was adjusted. Specific parameters are shown in Table 1.
[0233] 2. Performance Testing
[0234] 1. Negative electrode performance test
[0235] 1) Active specific surface area test
[0236] The negative electrode sheet prepared in the embodiment and comparative example was used as the cathode, the metal lithium sheet was used as the anode, and ferrocene at a concentration of 50 mmol / L was added to the electrolyte (the same electrolyte used in the battery preparation method), and then assembled into a button half-cell. Four parallel samples were taken and scanned at scan rates v of 0.1 mV / s, 0.3 mV / s, 0.5 mV / s, and 1 mV / s, respectively, to obtain cyclic voltammetry curves at different scan rates. The peak current ip of the cyclic voltammetry curve was extracted using EC-Lab software. With the square root of the scan rate v as the abscissa and the peak current ip as the ordinate, a linear plot of the cyclic voltammetry curve ip and the square root of the scan rate v was made to obtain its slope K.
[0237] According to the Randles-Sevick equation, the slope is: n represents the number of electron transfers, which is related to the type of probe molecule and is taken as 1; c represents the concentration of ferrocene and is taken as 50 mmol / L; D is the diffusion coefficient of ferrocene and is taken as 2.1×10 -6 cm 2 / s; then the active surface area of the negative electrode A=K / (2.69×10 5 ×n 2 / 3 cD 1 / 2 ), the ratio of the active surface area A of the negative electrode sheet to the weight m of the negative electrode sheet is the active specific surface area of the negative electrode sheet.
[0238] 2. Battery performance test
[0239] 1) Cycle test at 25°C until the capacity retention reaches 80%
[0240] The test process for the number of cycles required to achieve a capacity retention rate of 80% is as follows: At 25°C, the prepared battery is charged at a constant current of 1C to 3.65V, then charged at a constant voltage of 3.65V until the current drops to 0.1C, and then discharged at 1C to 2.5V. The resulting capacity is recorded as the initial capacity (C0). Repeat the above steps for the same battery and simultaneously record the discharge capacity (Cn) of the battery after the nth cycle. The battery capacity retention rate after each cycle is Pn = Cn / C0 × 100%. When Pn drops to 80%, the number of cycles of the battery is recorded.
[0241] 2) Rate performance test
[0242] At 25°C, the prepared battery was charged to 3.65V at a constant current rate of 0.5C, then charged at a constant voltage at 3.65V until the current was less than 0.05C, and allowed to stand for 5 minutes. The battery was then discharged to 2.5V at different rates of 0.2C, 1.0C, 1.5C and 2.0C. After each discharge, it was allowed to stand for 5 minutes, and the discharge capacity of the battery was recorded. Among them, the discharge capacity at a discharge rate of 0.2C was used as the benchmark, and 5 parallel samples were prepared for each group. The average value was taken, and the discharge capacity ratio of the battery at different discharge rates was calculated by the following formula. Battery rate discharge capacity ratio (%) = (discharge capacity at the corresponding rate / discharge capacity at a rate of 0.2C) × 100%
[0243] 3. Analysis of test results of various embodiments and comparative examples
[0244] Batteries of various examples and comparative examples were prepared according to the above methods, and various performance parameters were measured. The results are shown in Tables 1 and 2 below.
[0245] Table 1
[0246] Table 2
[0247] According to the above results, the electrolytes in Examples 1 to 41 all include the cyclic sulfate compound and the metal ion additive shown in Formula I, wherein R1, R2, R3, and R4 are independently selected from the structure shown in Formula II, hydrogen atoms, C 1- One of a C6 alkyl group, a halogen atom, a C1-C3 haloalkyl group, a C1-C3 alkoxy group, a C1-C3 haloalkoxy group, a double bond, an ester group, a cyano group, and a sulfonic acid group, and R1, R2, R3, and R4 are not simultaneously selected from a hydrogen atom;
[0248] In formula II, R5 and R6 are each independently selected from hydrogen atom, C 1- One of a C6 alkyl group, a halogen atom, a C1-C3 haloalkyl group, a C1-C3 alkoxy group, a C1-C3 haloalkyl group, a C1-C3 haloalkoxy group, a double bond, an ester group, a cyano group and a sulfonic acid group, and a wavy line indicates a bonding position.
[0249] From the comparison of Examples 1 to 29 with Comparative Examples 1 and 3, and Examples 30 to 41 with Comparative Examples 2 and 4, it can be seen that compared with the electrolyte containing only the cyclic sulfate compound or the metal ion additive represented by Formula I, the electrolyte of the present application includes both the cyclic sulfate compound and the metal ion additive represented by Formula I, which is beneficial to improving the ratio of the battery's 1.5C and 2C rate discharge capacity to the 0.2C discharge capacity, thereby improving the battery's rate performance.
[0250] From the comparison of Examples 1 to 29 with Comparative Example 5, and Examples 30 to 41 with Comparative Example 6, it can be seen that compared with the electrolyte comprising the cyclic sulfate compound represented by Formula III and the metal ion additive, the electrolyte of the present application comprises the cyclic sulfate compound represented by Formula I and the metal ion additive at the same time, which is beneficial to increasing the number of cycles of the battery with 80% capacity retention rate, and the ratio of 1.5C and 2C rate discharge capacity to 0.2C discharge capacity, thereby improving the cycle performance and rate performance of the battery.
[0251] From the comparison of Examples 1 to 6 and Comparative Example 5, and Examples 33 to 38 and Comparative Example 6, it can be seen that compared with the electrolyte including the cyclic sulfate compound represented by Formula III, the electrolyte including the cyclic sulfate compound represented by Formula I-1, I-2, I-6, I-7, I-8 or I-11 is beneficial to improving the number of cycles of the battery with 80% capacity retention rate, and the ratio of 1.5C and 2C rate discharge capacity to 0.2C discharge capacity.
[0252] As can be seen from Examples 4, 7-10, 33, and 36-39, based on the total mass of the electrolyte, the mass content W of the cyclic sulfate ester compound is controlled to satisfy the following: 0.001% ≤ W ≤ 20%, so that the battery has a higher number of cycles with 80% capacity retention, and the ratio of the 0.2C, 1C, 1.5C, and 2C rate discharge capacity to the 0.2C discharge capacity. From the comparison of Examples 4, 8-9 with Examples 7 and 10, and Examples 33, 37-38 with Examples 36 and 39, it can be seen that, based on the total mass of the electrolyte, further controlling the mass content W of the cyclic sulfate ester compound to satisfy the following: 0.1% ≤ W ≤ 5%, is conducive to further significantly improving the ratio of the battery's 1C rate discharge capacity to the 0.2C discharge capacity.
[0253] As can be seen from Examples 4, 11 to 15, the alkali metal ion content is controlled to be 30 ppm to 3000 ppm, based on the total mass of the electrolyte, so that the battery has a high 80% capacity retention cycle number and a high ratio of the discharge capacity at 0.2C, 1C, 1.5C, and 2C rates to the 0.2C discharge capacity. As can be seen from the comparison of Examples 4, 12 to 14 with Examples 11 and 15, further controlling the alkali metal ion content to be 50 ppm to 2000 ppm is beneficial to further improve the ratio of the battery's 1C rate discharge capacity to the 0.2C discharge capacity.
[0254] It can be seen from Examples 4 and 16 to 20 that, based on the total mass of the electrolyte, the mass content of high-valent metal ions is controlled to be 15 ppm to 300 ppm, so that the battery has a higher 80% capacity retention cycle number and a ratio of the discharge capacity at 0.2C, 1C, 1.5C and 2C rates to the 0.2C discharge capacity.
[0255] It can be seen from Examples 4 and 21 to 26 that, based on the total mass of the electrolyte, the mass content of alkaline earth metal ions is controlled to be 13 ppm to 500 ppm, so that the battery has a higher 80% capacity retention cycle number and a ratio of the discharge capacity at 0.2C, 1C, 1.5C and 2C rates to the 0.2C discharge capacity.
[0256] From the comparison of Examples 4, 27 to 29 with Comparative Example 1, and Examples 40 to 41 with Comparative Example 2, it can be seen that metal ion additives including sodium ions, copper ions, calcium ions, lithium ions, aluminum ions or magnesium ions are beneficial to improving the number of cycles of the battery with 80% capacity retention rate, and the ratio of 1C, 1.5C and 2C rate discharge capacity to 0.2C discharge capacity.
[0257] It can be seen from Examples 4 and 42 to 44 that the active specific surface area A of the negative electrode sheet is controlled to be ≤ 20 cm 2 / g, so that the battery has a higher 80% capacity retention cycle number and the ratio of the discharge capacity at 0.2C, 1C, 1.5C and 2C rates to the 0.2C discharge capacity. From the comparison of Examples 4, 42-43 and Example 44, it can be seen that the active specific surface area of the negative electrode sheet is further controlled to 5cm 2 / g~15cm 2 / g, which is beneficial to further improve the battery's 80% capacity retention cycle.
[0258] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. An electrolyte, characterized in that: The electrolyte comprises a cyclic sulfate compound as shown in Formula I and a metal ion additive, In Formula I, R1, R2, R3, and R4 are each independently selected from the group consisting of the structure shown in Formula II, a hydrogen atom, a C1-C6 alkyl group, a halogen atom, a C1-C3 haloalkyl group, a C1-C3 alkoxy group, a C1-C3 haloalkoxy group, a double bond, an ester group, a cyano group, and a sulfonic acid group, and R1, R2, R3, and R4 are not selected from the group consisting of a hydrogen atom at the same time; In formula II, R5 and R6 are each independently selected from a hydrogen atom, a C1-C6 alkyl group, a halogen atom, a C1-C3 haloalkyl group, a C1-C3 alkoxy group, a C1-C3 haloalkoxy group, a double bond, an ester group, a cyano group and a sulfonic acid group, and the wavy line indicates the bonding position.
2. The electrolyte according to claim 1, characterized in that R1, R2, R3, and R4 are each independently selected from the group consisting of a structure represented by formula II, a hydrogen atom, a C1-C6 alkyl group, a halogen atom, a C1-C3 haloalkyl group, a C1-C3 alkoxy group, and a cyano group.
3. The electrolyte according to claim 1 or 2, characterized in that R1 is selected from a hydrogen atom, a C1-C3 alkyl group; R2 is selected from C1-C3 alkyl, halogen atom, C1-C3 haloalkyl, cyano or the structure shown in formula II; R3 is selected from a hydrogen atom, a C1-C3 alkyl group; R4 is selected from a C1-C3 alkyl group, a halogen atom, a C1-C3 alkoxy group or a structure represented by formula II.
4. The electrolyte according to any one of claims 1 to 3, characterized in that R1 is selected from a hydrogen atom or a methyl group; R2 is selected from methyl, ethyl, fluorine, trifluoromethyl, cyano or the structure shown in formula II; R3 is selected from a hydrogen atom; R4 is selected from methyl, ethyl, propyl, fluorine atom, ethoxy or the structure shown in formula II.
5. The electrolyte according to any one of claims 1 to 4, characterized in that R1 and R3 are hydrogen atoms; R2 and R4 are methyl, ethyl, fluorine atoms or the structure shown in Formula II; or, R2 is methyl or the structure shown in formula II, and R4 is methyl.
6. The electrolyte according to any one of claims 1 to 5, characterized in that R1 and R3 are hydrogen atoms; R2 and R4 are methyl or a structure shown in Formula II.
7. The electrolyte according to any one of claims 1 to 6, characterized in that R5 and R6 are each independently selected from a hydrogen atom and a C1-C3 alkyl group.
8. The electrolyte according to any one of claims 1 to 7, characterized in that The cyclic sulfate compound is selected from one or more of the following compounds:
9. The electrolyte according to any one of claims 1 to 8, characterized in that Based on the total mass of the electrolyte, the mass content W of the cyclic sulfate ester compound satisfies: 0.001%≤W≤20%, and can be optionally 0.1% to 5%.
10. The electrolyte according to any one of claims 1 to 9, characterized in that The metal ion additive includes one or more of alkali metal ions, alkaline earth metal ions and high-valent metal ions.
11. The electrolyte according to claim 10, characterized in that The alkali metal ions include one or more of sodium ions, lithium ions, and potassium ions; and / or Based on the total mass of the electrolyte, the mass content of the alkali metal ions is 30 ppm to 3000 ppm, and can be optionally 50 ppm to 2000 ppm.
12. The electrolyte according to claim 10 or 11, characterized in that: The high-valent metal ions include one or more of aluminum ions and copper ions; and / or Based on the total mass of the electrolyte, the mass content of the high-valent metal ion is It is 0.5ppm~300ppm, and can be optionally 15ppm~200ppm.
13. The electrolyte according to any one of claims 10 to 12, characterized in that The alkaline earth metal ions include one or more of magnesium ions and calcium ions; and / or Based on the total mass of the electrolyte, the mass content of the alkaline earth metal ions is 0.5 ppm to 500 ppm, and can be optionally 13 ppm to 400 ppm.
14. The electrolyte according to any one of claims 1 to 13, characterized in that The electrolyte solution further includes an electrolyte salt, and the electrolyte salt includes a lithium salt or a sodium salt; The lithium salt includes one or more of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorobis(oxalate)phosphate, and lithium dioxalateborate; The sodium salt includes one or more of sodium hexafluorophosphate, sodium difluorooxalatoborate, sodium perchlorate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethanesulfonyl)imide, and sodium trifluoromethanesulfonate.
15. A secondary battery, characterized in that: The invention comprises a negative electrode sheet and the electrolyte according to any one of claims 1 to 14.
16. The secondary battery according to claim 15, characterized in that: The secondary battery includes a sodium battery or a lithium battery.
17. The secondary battery according to claim 15 or 16, characterized in that: The negative electrode plate includes a negative electrode active material, and the negative electrode active material includes one or more of artificial graphite, natural graphite, hard carbon, soft carbon, mesophase carbon microspheres, carbon fibers, carbon nanotubes, elemental silicon, silicon oxides, silicon-carbon composites, silicon alloys, elemental tin, tin oxides, and titanium composites.
18. The secondary battery according to any one of claims 15 to 17, characterized in that: The active specific surface area A of the negative electrode plate and the mass content W of the cyclic sulfate compound satisfy: 0.0002cm 2 / g≤W×A≤0.04cm 2 / g, optionally, 0.02cm 2 / g≤W×A≤0.1cm 2 / g.
19. The secondary battery according to claim 18, characterized in that: The active specific surface area A of the negative electrode sheet satisfies: A≤20cm 2 / g, optional 5cm 2 / g~15cm 2 / g.
20. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 15 to 19.
Citation Information
Cited By
Composite nickel cobalt lithium manganate positive electrode active material, preparation method thereof and high-rate low-temperature-rise full-tab lithium battery
CN121583894A
Preparation method of ethylene trisulfate
CN121627634A
A method for preparing vinyl trisulfate
CN121627634B